Academic Senate Minutes 2011-02-24 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 2/10/11 approved. New Statistics minor; Revision to Math minor; Engineering Science name change; Revision to Anthropology minor approved. President Report. Chair-Elect Report. Resolution on Creating a Gender and Sexual Health Stakeholder's Exploratory Committee approved. Revision to the RTP Policy approved. FSAC Report. Provost Report. Statewide Senator Report. Associated Students Report. Vice President Report. Good of the Order.